(Table T1) Paleomagnetic characterization of ODP Hole 198-1213B basalts - Tominaga, Masako; Sager, William W; Channell, James E T (Supplement to: Tominaga, M et al. (2005): Paleomagnetism of the igneous section, Hole 1213B, Shatsky Rise. In: Bralower, TJ; Premoli Silva, I; Malone, MJ (eds.) Proceedings of the Ocean Drilling Program, Scientific Results, College Station, TX (Ocean Drilling Program), 198, 1-15, https://doi.org/10.2973/odp.proc.sr.198.113.2005, 2005)
Paleomagnetic measurements were made on 52 samples from the igneous section of Ocean Drilling Program Hole 1213B for the purpose of determining paleoinclination and polarity and giving insight about volcanic emplacement. Samples were taken at approximately even intervals from the three basaltic sills that make up the section, and all samples were demagnetized using an alternating field or thermal methods in an effort to determine the characteristic magnetization direction. Half of the samples gave inconsistent results. Furthermore, natural remanent magnetization values were strong and median destructive field values were low, implying that the basalts are prone to acquiring an overprint from the drill string. In addition, hysteresis results show low coercivities and lie in the pseudosingle-domain field of a Day plot (Mr/Ms vs. Bcr/Bc). All of these observations suggest that the samples are characterized by a low-coercivity magnetic mineral, such as titanomagnetite, that may not always preserve a stable characteristic remanence. Nevertheless, 26 samples produced consistent inclinations, giving shallow, negative values that are considered the likely characteristic direction. There is no statistical difference between mean inclinations for the three units, implying they erupted within a short time. Measurements from all reliable samples were averaged to give a paleoinclination of -9.3° with 95% confidence limits from -41.8° to 27.5°, the large uncertainty resulting from the fact that paleosecular variation is not averaged. Although the large uncertainty makes a unique assignment of polarity difficult, the interpretation that is most consistent with other Pacific paleomagnetic data is that the magnetization has a reversed polarity acquired slightly north of the equator.